Getting ahead : a communication skills course for business English with answers (Student's book) - Jones-Macziola, Sarah; Lê Ngọc Phương Anh, MA.; Ban biên dịch First News. (Đà Nẵng : Nxb Đà Nẵng, 2003)
Introductions and greetings; Occupations; Companies; The place of work; Revision and consolidation; ...
Keywords: English language; Business English; English language -- Business language